International Symposium on Optoelectronic Technology and Application 2014: Laser Materials Processing; And Micro/Nano Technolog 2014
DOI: 10.1117/12.2070830
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength properties of DCG holograms under the conditions of different temperature and humidity

Abstract: Holograms recorded in dichromated gelatin (DCG) are usually sealed with a glass plate cemented with an epoxy glue to protect the holograms from moisture in the environment. An investigation of the wavelength properties of sealed DCG holograms had been carried out paying attention to holograms which were exposed to different temperature and humidity environment in this work. The investigation had revealed that (a) exposing the sealed DCG holograms to high relative humidity (RH=98%) environment or immersing them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This material experiences a red wavelength shift in its diffraction response with increased temperature and humidity. Liu et al [21] investigated the spectral properties of the DCG-based holograms under different temperatures and humidity conditions. They found that the peak diffracted wavelength decreased with temperature and thermal processing time.…”
Section: Introductionmentioning
confidence: 99%
“…This material experiences a red wavelength shift in its diffraction response with increased temperature and humidity. Liu et al [21] investigated the spectral properties of the DCG-based holograms under different temperatures and humidity conditions. They found that the peak diffracted wavelength decreased with temperature and thermal processing time.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers were proposed in recent years to research on the principles and applications about the holographic grating used as the optic combiner or waveguide. [1][2][3][4][5] A typical scheme for VHG used in a HMD was shown in Fig.1. As shown in Fig.1 the rays emitted by the micro display were entered into in-couple grating with different angles after collimating.…”
Section: Introductionmentioning
confidence: 99%